Old Meets New: Mass Spectrometry-Based Untargeted Metabolomics Reveals Unusual Larvicidal Nitropropanoyl Glycosides from the Leaves of Heteropterys umbellata - Mannochio-Russo, Helena [UNESP]; Nunes, Wilhan D. G.; Almeida, Rafael F.; Albernaz, Lorena C.; Espindola, Laila S.; Bolzani, Vanderlan S. [UNESP] (American Chemical Society (ACS), 2023)
The Aedes aegypti (Diptera: Culicidae) mosquito is the vector of several arboviruses in tropical and subtropical areas of the globe, and synthetic pesticides remain the most widely used combat strategy. This study describes the investigation of secondary metabolites with larvicidal activity from the Malpighiaceae taxon using a metabolomic and bioactivity-based approach. The workflow initially consisted of a larvicidal screening of 394 extracts from the leaves of 197 Malpighiaceae samples, which were extracted using solvents of different polarity, leading to the selection of Heteropterys umbellata for the identification of active compounds. By employing untargeted mass spectrometry-based metabolomics and multivariate analyses (PCA and PLS-DA), it was possible to determine that the metabolic profiles of different plant organs and collection sites differed significantly. A bioguided approach led to the isolation of isochlorogenic acid A (1) and the nitropropanoyl glucosides karakin (2) and 1,2,3,6-tetrakis-O-[3-nitropropanoyl]-beta-glucopyranose (3). These nitro compounds exhibited larvicidal activity, possibly potentialized by synergistic effects of their isomers in chromatographic fractions. Additionally, targeted quantification of the isolated compounds in different extracts corroborated the untargeted results from the statistical analyses. These results support a metabolomic-guided approach in combination with classical phytochemical techniques to search for natural larvicidal compounds for arboviral vector control.